Menghitung Kembali Kontribusi Perladangan Berpindah dalam Proses Penyusutan Kawasan Hutan di Indonesia - R. Yando Zakaria; Djaka Soehendera (Antropologi Indonesia, 1997)
In the last two decades, deforestation - especially tropical rain forest - becomes the main issue due to the future of mankind. In Indonesia, deforestation increased from 300,000 ha/year in 1970s to 600,000 ha/year in 1980s. Some people argue that shifting cultivation plays important role in this deforestation. Yet, there is methodological constraint to obtain the best figure of deforestation caused by shifting cultivators, namely too exaggerated and unacceptable. Hence, the authors suggest some aspects that can be taken into consideration in calculating contribution of shifting cultivation to deforestation in Indonesia such as population dynamic, technological change, introducing cash crop, presence of migrant cultivator, and transmigration program.